(untitled) (Research, Society and Development, 2024)
Objective: To analyze the effects of neuromuscular training on proprioception after anterior cruciate ligament reconstruction (ACLR). Methods: Systematic review, described based on the PRISMA flowchart, including randomized clinical trials in Portuguese, English or Spanish, published between 2012 and 2023, using the PICO strategy. 706 articles were found through the Pubmed, Embase, Web of Science, Science Direct, Scopus and Cochrane Library databases. To assess the quality of randomized clinical trials, the PEDro Scale was used. Results: The studies carried out different training sessions with varied resources, using variables such as joint position sense (JPS), postural control and balance to evaluate the proprioceptive effects of the training. The comparison groups underwent conventional rehabilitation or were healthy. In one study, joint position sense did not show a significant difference between the operated and non-operated sides, but there was a significant difference between the operated sides. Aquatic and land-based proprioceptive training compared to the group that performed conventional therapy showed proprioceptive improvement. The comparison of the balance training group with healthy people showed a partial improvement in dynamic stability indices. Cross balance exercises showed improvement in static and dynamic balance. Whole body vibration therapy did not show an improvement in joint position sense, but it did show an improvement in postural balance. Final considerations: It was possible to identify that the different types of training demonstrated positive effects with significant improvement in outcomes such as joint position sense, postural control, static balance and dynamic balance, after ACLR.